PENENTUAN STRATEGI PEMASARAN MENGGUNAKAN ANALISIS SWOT UNTUK MENINGKATKAN PENGGUNAAN JASA RENOVASI SINAR LASER - Adinata, Davin Kurniawan (Jurnal Performa: Jurnal Manajemen dan Start-up Bisnis, 2017)
This study aims to determine the marketing strategy using SWOT analysis to increase the use of Sinar Laser Renovation Services. The cornerstone of the theory used in this study is a marketing strategy, Porter's five force analysis, SWOT Analysis and Marketing Mix. The research method used in this study is a qualitative research design with case study approach. This study uses four resource persons as research subjects, which consisted of one person owner Sinar Laser, one person of Sinar Laser’s project supervisor, and two people from the company’s benchmark. The validity and reliability analysis of this study is using member’s check techniques. The results of the Porter's 5 Force analysis show that the threat of new entrants is high enough for Sinar Laser, the bargaining power of suppliers for Sinar Laser is fairly low, the bargaining power of consumers is high, companies such as interior design or civil work which currently increasing could be a threat of products substitute for Sinar Laser’s business in Surabaya, business competition faced by Sinar Laser is very high. Furthermore, the SWOT analysis results indicate that the Sinar Laser is in the “turn-around” position, therefore marketing strategies can be used are: add more employees, offer services at low prices, opening the offices of Sinar Laser near the construction area and add more connections to expand the market.